BENTUK–BENTUK GAYA BAHASA HIPERBOLA DALAM NOVEL KAMI BUKAN SARJANA KERTAS KARYA J.S. KHAIREN - Wahyuni, Uli; Alam, Futri (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
The background of this research is the increase use of hyperbola style in J.S. Khairen’s novel which is quite interesting to the writer because it tells about the lives of students who struggle for the future despite being forced to study on an unknown private campus. This research aims to describe the forms of hyperbole style and the meaning of hyperbole style in the novel Kami Bukan Sarjana Kertas by J.S. Khairen. The approach used is descriptive related to the study and focuses on the forms of hyperbole occurred in the novel. The technique used is the document technique with the approach of content analysis as a data analysis technique. Based on data analysis found that the nove obtained forms of hyperbole style with quite a lot of, namely, numbering as many as 71 quotes. Furthermore, the style of hyperbole has a very important role in the story of Kami Bukan Sarjana Kertas by J.S. Khairen, namely the style of writing, giving a certain emphasis on the problems that J.S. Khairen wants to convey as a novel author, strengthening the impression for the reader on an event or character of the characters in the story, bringing the story to life and beautifying the story in the novel.